2018
DOI: 10.1186/s12887-018-1011-4
|View full text |Cite
|
Sign up to set email alerts
|

Supporting play exploration and early developmental intervention versus usual care to enhance development outcomes during the transition from the neonatal intensive care unit to home: a pilot randomized controlled trial

Abstract: BackgroundWhile therapy services may start in the Neonatal Intensive Care Unit (NICU) there is often a gap in therapy after discharge. Supporting Play Exploration and Early Development Intervention (SPEEDI) supports parents, helping them build capacity to provide developmentally supportive opportunities starting in the NICU and continuing at home. The purpose of this single blinded randomized pilot clinical trial was to evaluate the initial efficacy of SPEEDI to improve early reaching and exploratory problem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 42 publications
(33 reference statements)
1
51
0
4
Order By: Relevance
“…Systematic review evidence indicates that a small effect on motor outcomes is gained for infants 0–2 years with brain injuries, when interventions are applied that enrich at least one aspect of the environment (social, motor, sensory, or cognitive) (Morgan et al, 2013). Since this review, two further studies of preterm infants (with and without brain damage) (Dusing et al, 2015, 2018) have shown early promising results in early problem solving skills. “SPEEDI” (Supporting Play Exploration and Early Developmental Intervention) is an intervention where parents are coached and supported to promote daily movement opportunities and environmental enrichment strategies with their infant.…”
Section: Emergent Interventionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Systematic review evidence indicates that a small effect on motor outcomes is gained for infants 0–2 years with brain injuries, when interventions are applied that enrich at least one aspect of the environment (social, motor, sensory, or cognitive) (Morgan et al, 2013). Since this review, two further studies of preterm infants (with and without brain damage) (Dusing et al, 2015, 2018) have shown early promising results in early problem solving skills. “SPEEDI” (Supporting Play Exploration and Early Developmental Intervention) is an intervention where parents are coached and supported to promote daily movement opportunities and environmental enrichment strategies with their infant.…”
Section: Emergent Interventionsmentioning
confidence: 98%
“…These interventions may be delivered during the NICU stay (Ustad et al, 2016) or commence post discharge (Spittle et al, 2010). Some intervention studies start during NICU admission and continue for a short period after discharge (Dusing et al, 2015, 2018). Since it is clear that prematurity significantly impacts all developmental domains, in most instances study inclusion is based on gestational age or birthweight.…”
Section: Emergent Interventionsmentioning
confidence: 99%
“…Third, neonatal therapy services can provide support to parents and help them in navigating through the challenges of the unexpected arrival of their child before term, adjusting to the NICU environment, a long‐term hospital stay, and the probability of risk of developmental delays. Supporting and engaging parents in the implementation of an intervention program empowers them, which leads to an increase in self‐efficacy and a decrease in anxiety and depressive symptoms that have been associated with better developmental outcomes of at‐risk infants . A Cochrane review on the efficacy of early intervention programs provided in the first year of life concluded that interventions focused on parent–child collaboration had better developmental outcomes compared to when the intervention was solely focused on either parent or infant .…”
Section: Operational Definitionsmentioning
confidence: 99%
“…In addition to heterogeneity, a lack of clarity in neonatal therapy research makes synthesizing the findings difficult. The key principles and efficacy of neonatal therapy, specifically provided by physical therapists, occupational therapists, or speech‐language pathologists, has not been quantified in a systematic fashion . Thus, the purpose of this review was to identify and evaluate studies where neonatal therapy was initiated in the NICU, as provided or designed by a physical, occupational, or speech therapist, and report the effect of the intervention on the behavioral, motor, and cognitive outcomes of child development.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…While the provision of developmental neuroprotective care is a fundamental neonatal nursing responsibility, the five core measures included in the 2011 NANN guidelines serve as imperatives that an optimal neuroprotective environment requires the coordination of care with disciplines of medicine and nursing, including the scope of practice of NTs [18][19][20][21][22][23]. Skilled neonatal therapy competencies support preventative intervention from birth to enhance physiologic function and neurostructural development of the infant with benefits extending to all stakeholders including the infant, family, healthcare community, and provider networks [11,[24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%